134 Meta-analysis to Determine the Effects of Particle Size on Nursery and Finishing Pig's Growth Performance and Stomach Morphology. (7th May 2021) - Kippert, Carlos J; Vier, Carine M; Lu, Ning; Cast, Wayne R; Navales, Ron A; Dritz, Steve S; Orlando, Uislei A
Abstract: A meta-analysis was conducted to determine grain particle size (PS) effects on pig growth performance and stomach morphology. Data from 29 trials (11 in the nursery and 18 in the finisher) published from 1986 to 2016 for a total of 140 observations were recorded in a database. The response variables were average daily gain (ADG), average daily feed intake (ADFI), gain-to-feed ratio (G:F), ulceration and keratinization scores. Tested predictors included the interactions between PS linear and quadratic effects, production phase, diet form, and main effects of grain type, ingredient inclusion, and mill type. Trial was included as a random effect. Data were analyzed with the lmer function from the lme4 package in R. Significant predictors (P < 0.05) and with improved model fit remained in the final model. Results indicated a significant interaction (P < 0.05) between diet form and quadratic PS for ADFI and G:F. Nursery and finishing pigs fed meal diets linearly reduced ADFI and improved G:F as PS reduced. Nursery pigs fed pelleted diets had reduced ADFI and improved G:F with PS reduced to 500–600µ, with increased ADFI and poorer G:F at lower PS. Finishing pigs fed pelleted diets had reduced ADFI and improved G:F with PS reduced to 500–600µ, with no further changes at lower PS. Regardless of diet form and production phase, ADG increased (quadratic, P < 0.05) as PS reduced until approximately 600µ and decreased at lower PS. There was no evidence of PS effect on ulceration score (P = 0.12). Keratinization score increased (P < 0.05) as PS decreased. Reducing PS in meal diets linearly increased keratinization scores, reduced ADFI, and improved G:F. However, no further benefits in performance were observed at grain PS below 500–600µ in pelleted diets.